A PRELIMINARY RESULTS ON THE CONTROL OF CERCOSPORA LEAF SPOT ATTACK IN SOME SUGAR BEET HYBRIDS WITH DIFFERENT DOSES OF FUNGICIDES - Manuela Hermeziu; Lorena Adam; Diana Petre; Carmen Chelmea (Agricultura)
To the National Institute of Research and Development for Potato and Sugar Beet Brasov, in 2023, two polyfactorial experiments were carried out on the sugar beet crop which aimed to determine the effect of fungicides, full dose, respectively half dose, on beet plants affected by the pathogen Cercospora beticola. The experiments included five variants each, an untreated (control) variant, two variants with the recommended dose of fungicide (250 g/l difenoconazole active substance, respectively 14.1 g/l Bacillus subtilis strain QST 713) and two variants with 50% of the recommended fungicides dose. Four treatments were performed at an interval of 14 days, starting on July 14th. The assessment of Cercospora leaf spot attack intensity were made using a scale of 1 to 9. The highest efficacy was presented by Score fungicide applied at full dose (94.74%, respectively 93.33%), and the lowest by Serenade at half dose (80.26%, respectively 78.67%). Also, the yield obtained was between 70.75 t/ha to Score full dose (Belamia hybrid) and 43.75 t/ha for the control variant (Rosadda hybrid). The sugar content of the experimental varieties ranges between 13.90% (untreated Belamia hybrid) and 17.10% (Score product to Rosadda hybrid). The aim of our research was to investigate the way in which the obtained results offer technological solutions to farmers to contribute to increasing the economic efficiency of sugar beet cultivation.